Development of Hematite-based photoanodes - Rodrigues, Murillo Henrique de Matos (2023)
Hydrogen production via Water Splitting has been considered one of the best solutions for energy shortages and environmental pollution. The use of hematite (α-Fe2O3) as a photoanode in photoelectrochemical hydrogen production processes has been increasingly studied due to its high stability, non-toxicity, absorption in the region up to 600 nm (covering up to 40% of the solar energy spectrum), low bandgap values (between 1.9 - 2.2 eV), high accessibility and low cost, considering that iron is the fourth most abundant element in the Earth's crust. Current density studies show that hematite has a photocurrent of 12.6 mA cm-2 under solar irradiation, reaching 16% efficiency in photoelectrochemical processes in water separation. However, it has some limitations in its effectiveness due to low electronic mobility, low electrical conductivity, between 10-14 - 10-6 Ω-1cm-1, high surface state density, and slow reaction kinetics. Among the methods used for processing the hematite photoanode, we can highlight the thin films from the colloidal deposition of magnetic nanoparticles. This technique leads to the production of high-performance hematite photoanode. However, little is known about the influence of the magnetic field and heat treatment parameters on the final properties of hematite photoanodes. Thus, the first part of the work evaluated how these processing parameters in the morphology and photoelectrochemical properties of nanostructured hematite anodes. The thickness analysis demonstrated a relationship between the magnetic field and the concentration of nanoparticles used to prepare the thin films, showing that larger magnetic fields decrease the thickness. Jabs's results corroborate the existence of the influence of the magnetic field since the use of a larger magnetic field decreases the amount of deposited material, consequently decreasing the optical absorption of thin films. PEC measurements showed that at higher concentrations, using higher magnetic fields increases JPH values, and lower magnetic fields cause a decrease in JPH when using higher concentrations of nanoparticles. Even controlling the thickness and morphology of the iron oxide-based films, the pure material has a high recombination of photogenerated charge due to its low charge separation efficiency, which can generate poor electronic transport, which has hindered its commercial application. Based on the limitations of hematite, the second part of the study was to study germanium as a potentially ideal element that combines improved charge transfer efficiency and morphology control for high-performance hematite-based photoanode. Intensity-modulated photocurrent spectroscopy (IMPS) results demonstrated that the addition of Ge increased charge mobility, leading to superior charge separation efficiency compared to pure hematite photoanode. C-AFM (Conductive Atomic Force Electron Microscopy) measurements demonstrate that Ge improves electron conductivity and increases majority carrier mobility. Photoelectrochemical measurements performed at different wavelengths show that Ge interferes with the formation of small polarons, making the charges more mobile (delocalized), thus favoring the separation process of photoinduced charges. The synergistic role played by the addition of Ge resulted in a significant improvement in photoelectrochemical performance from 0.5 to 3.2 mA cm-2 at 1.23 VRHE, comparing original and Ge-hematite-based photoanodes, respectively.